Manifest: 2005 year of sport and Physical Education. (Journal of Parents and Teachers, 2014)
From UNICEF, the value of play is acclaimed as a fundamental right of childhood and, therefore, sports is promoted as a powerful tool to achieve, among others, gender equality or social integration.
Keywords: UNICEF; game; sport; tool; society.